Antibiotic Resistance of Staphylococcus Sp. Isolated from Air, Surface, Food and Clinical samples Collected from Baghdad Hospital (Baghdad Science Journal, 2023)
Staphylococcus Sp.is the most common type of bacteria found in contamination place, we design this study to compare the contamination accident between two hospitals in Baghdad.One of them isthe Burns Specialist Hospital in the Medical CityinRusafa and another one is Al-Karama Hospital in Karkh. The samples were collected fromOperativeWard No1 (OW1), Operative Ward No2 (OW2), Consulting Pharmacy (CP), Emergency Room (ER), Reception Room (RR), Women's Ward (WW) and Men's Ward (MW).The samples were taken from inside each clinical unit, surfaces, food, and air. The results showed that the number of samples containing Staphylococcus sp. bacteria is 81, including 45 belonging to Al-Karama Burns Ward Hospital and 36 belonging to the Medical City Hospital, Burns Special Hospital. The results of Medical City Hospital showed that Staphylococcus sp.isolates resist many antibiotics, 99.99% of the isolatesfrom patient samples were resistant to(CLR, P, AMP); 92.30% of the isolates from air samples were resistant to(P, MET) and 85.71%of isolates from surfaces and food samples were resist for (AMP, MET). Also the results of Al-KaramaHospital showed that the highest resistance in the staphylococcus sp.isolateswere in patient samplesfor (AMP, SXT), in surface samples for (E), in food samples for (E,P) and in air samples for (P) and the resistance rates were 100% to all these antibiotics.